Monocular Vision Loss Relating to Impaired Binocular Vision. - Eryou, April (Optometry & Visual Performance, 2025)
Background: Acquired monocular vision loss, either traumatic or from a disease process, can impair binocular viewing. Impaired binocular viewing can negatively affect visual performance and quality of life. This case report demonstrates the combined use of sectoral occlusion, neurooptometric rehabilitation therapy, and syntonics therapy in the rehabilitation of a patient with monocular vision loss due to a retinal detachment secondary to diabetic retinopathy. Case Report: A fifty-year-old Jamaican female presented for a neuro-optometric evaluation following the treatment of a diabetic retinopathyinduced retinal detachment in her left eye. She underwent two surgeries in her left eye and had reduced acuity, severe dry eye, and glaucoma. Her chief complaints were that the vision in her left eye was poor/blurry; with binocular viewing, her vision was "shaky;" and she was experiencing diplopia. The optometric evaluation revealed an intermittent alternating exotropia, with a preference for the left eye to attempt fixation; an oculomotor dysfunction; and a visual processing dysfunction. Treatment included nine sessions of neuro-optometric rehabilitation therapy, including sectoral occlusion, updated spectacle lens prescription, and syntonics therapy. Following treatment, the patient was able to begin a return-to-work program. Conclusion: Despite having a fully functioning second eye, patients with monocular vision loss can have impaired visual performance due to presumed binocular inhibition. This case report that neuro-optometric rehabilitation therapy can successfully treat binocular inhibition and help these patients regain visual performance.